Fostering patriotism through education on the conservation of Indonesian endemic animals to students in Selangor, Malaysia - Randi Syafutra (Community Empowerment, 2024)
Indonesia, the world's largest archipelago with rich biodiversity, faces significant challenges in conserving endemic animals such as the Komodo dragon, Sumatran tiger, Bornean orangutan, and Javan rhinoceros. This Community Service (CS) program aimed to raise awareness and knowledge among Indonesian students abroad, particularly in Selangor, Malaysia, about the importance of conserving these animals. The program comprised four stages: a pre-test, educational sessions, a virtual tour, and a post-test. Results showed a significant increase in students' understanding, with the post-test average score reaching 85%, compared to 40% on the pre-test. The educational sessions successfully motivated students to participate in conservation efforts, demonstrating the effectiveness of the educational and participatory approach.